Prevalence of different types of accessory canals in the furcation area of third molars - Zuza, Elizangela P.; Toledo, Benedicto E. C.; Hetem, Sebastiao; Spolidório, Luis Carlos [UNESP]; Mendes, Ary J. D.; Rosetti, Elizabeth P. (Amer Acad Periodontology, 2006)
Background: Although there are several studies that show the prevalence and diameter of accessory root canals in the furcation area, there is a scarceness of studies that observe the trajectory and different types of cavo-interradicular canals. The aim of this study was to verify the prevalence of the different morphologic types of accessory canals in the furcation region in an attempt to show their trajectories.Methods: Forty submerged mandibular third molars were used, which were extracted and decalcified so that the microtomy procedure in the mesio-distal axial plane could be performed, obtaining semiserial sections with thicknesses of 5 mu m. The sections were stained with hematoxylin and eosin and observed under optical microscopy.Results: All of the morphologic types were found, whereas the proper accessory canals, type-A canals, were present in 10% of the specimens. The most prevalent canals were the sealed ones (type D), with a prevalence of 87.5%, followed by the blind ones (type B), with a prevalence of 75%. The loop accessory canals (type C), observed in only 5% of the teeth, were the least prevalent ones.Conclusions: Different morphologic types of accessory canals were found in the furcation area of submerged mandibular molars. The histologic method was effective to show the canal trajectories.
Keywords: dental pulp; periodontal ligament